PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH MERGER DAN AKUISISI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putri Anani; RM. Riadi; Gusnardi Gusnardi (Jurnal GeoEkonomi, 2022)
Entering the era of globalization at this time and with the enactment of the free market, competition in the business world or business is getting tighter. This condition requires companies to be able to develop strategies. One strategy that can be done by the company is by conducting mergers and acquisitions. However, often the failure or deteriorating performance of the company occurs after the company conducts mergers and acquisitions. The purpose of this study is to compare the company's financial performance before and after mergers and acquisitions. This type of research is comparative research. The population in this study are all public companies listed on the IDX that have conducted mergers and acquisitions in the 2015-2016 period as many as 15 companies. The sample of this study amounted to 6 companies. The sampling technique used purposive sampling. This study uses secondary data. Data collection technique is documentation. The data analysis technique used is the Wilcoxon Signed Rank Test and thetest Manova. The results showed that partially there was no significant difference in the company's financial performance before and after mergers and acquisitions based on financial ratios, namely NPM, ROA, ROE, DER, EPS and TATO before mergers and acquisitions. Simultaneously there is no significant difference in the company's financial performance as measured by all financial ratios of NPM, ROA, ROE, DER, EPS and TATO before mergers and acquisitions.